Market power in international emissions trading : the impact of U.S. withdrawal from the Kyoto Protocol - Christoph Böhringer; Andreas Löschel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
This paper investigates the implications of U.S. withdrawal on environmental effectiveness, economic efficiency, and the distribution of compliance costs taking into account market power of the Former Soviet Union (FSU) on emission permit markets. While exercise of market power on behalf of FSU under U.S. compliance has no environmental impact as compared to competitive permit trade, it prevents the Kyoto Protocol from boiling down to business-as-usual after U.S. withdrawal. Non-compliance of the U.S. increases the efficiency losses from FSU market power and reduces the compliance costs of remaining OECD countries but these gains must be weighted against a dramatic loss in overall environmental effectiveness. Clearly, the big losers from U.S. withdrawal are FSU and its competitive fringe (Central and Eastern Europe) that suffer from a huge decline in permit sales revenues.
Keywords: Q58; Q43; D58; 330; climate policy; emission trading; market power; Klimaschutz; Internationale Umweltpolitik; Emissionsrechte; Marktmacht; Wirtschaftliche Effizienz; Folgekosten; Welt; USA; Sowjetunion - Nachfolgestaaten; Russland